Multilayer ceramic capacitor and method of manufacturing same
By introducing a concentrated Mg area into the capacitor body of the multi-layer ceramic capacitor and controlling the magnesium distribution of the dielectric layer, the reliability problem under thin dielectric layer conditions is solved, and excellent acceleration life reliability of high capacity and small capacitors are achieved.
Patent Information
- Application Number
- CN202410671709.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-11-08
- Filing Date
- 2024-05-28
- Publication Date
- 2025-05-09
AI Technical Summary
When designing high-capacity and small multi-layer ceramic capacitors, how to ensure reliability characteristics under thin dielectric layer conditions, especially how to uniformly distribute additives and control grain growth, thereby improving the reliability of the capacitor.
By introducing a Mg concentration region into the capacitor body of the multi-layer ceramic capacitor and controlling the atomic percentage content of magnesium (Mg) in adjacent regions of the interface of the dielectric layer, a missing portion of the inner electrode layer is formed to increase the barrier height at the interface between the dielectric layer and the inner electrode layer.
The excellent acceleration life reliability of the multi-layer ceramic capacitor is achieved, and the oxygen vacancies concentration is reduced, thereby improving the reliability of the capacitor by suppressing the excessive use of magnesium elements in the dielectric layer.
Smart Images

Figure CN119964984A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a multilayer ceramic capacitor and a method of manufacturing the same. Background Art
[0002] Electronic components using ceramic materials include capacitors, inductors, piezoelectric elements, varistors, or thermistors. Among such ceramic electronic components, multilayer ceramic capacitors (MLCCs) are used in various electronic devices due to their small size, high capacity, and ease of mounting.
[0003] For example, multilayer ceramic capacitors may be chip capacitors mounted in boards of various electronic products to be charged or discharged, including imaging devices such as liquid crystal displays (LCDs), plasma display panels (PDPs), and organic light emitting diode (OLED) displays, computers, personal portable terminals, and smart phones.
[0004] Recently, multilayer ceramic capacitors require high performance and miniaturization. In order to achieve high-capacity and small multilayer ceramic capacitors, it is necessary to make the dielectric layer thinner. In order to ensure reliability characteristics under the design conditions of thin dielectric layers, it is important to uniformly distribute additives and control grain growth, and it is important to control the distribution and content ratio of additive elements that contribute to improving reliability. Summary of the invention
[0005] The present disclosure provides a multilayer ceramic capacitor having excellent accelerated lifetime reliability.
[0006] The present disclosure provides a method of manufacturing a multilayer ceramic capacitor.
[0007] One aspect of the present disclosure provides a multilayer ceramic capacitor, the multilayer ceramic capacitor comprising: a capacitor body including a dielectric layer and an inner electrode layer; and an outer electrode disposed on the capacitor body. The capacitor body includes at least one missing portion, the missing portion is defined as a region where the continuity of the inner electrode layer is disconnected, and the missing portion includes a Mg concentration region, the Mg concentration region includes magnesium (Mg) as a main element, the dielectric layer includes an interface adjacent region, the interface adjacent region is defined as a region from an interface between the dielectric layer and the inner electrode layer to a position in the dielectric layer at a depth of 80nm to 100nm, and the interface adjacent region includes magnesium (Mg), and the atomic percentage content of magnesium (Mg) included in the interface adjacent region of the dielectric layer is lower than the atomic percentage content of magnesium (Mg) included in the Mg concentration region of the missing portion.
[0008] An amount of magnesium (Mg) included in the Mg concentrated region may be 1.6 atomic % to 11.1 atomic % based on the total amount of components of the Mg concentrated region of the missing portion.
[0009] The Mg concentrated region of the missing portion may also include barium (Ba), titanium (Ti), nickel (Ni), dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), aluminum (Al), silicon (Si), tin (Sn), oxygen (O) or a combination thereof.
[0010] The Mg concentrated region of the missing portion may further include titanium (Ti), and an amount of magnesium (Mg) included in the Mg concentrated region of the missing portion may be 12.68 to 22,000 parts by mole based on 100 parts by mole of titanium (Ti) in the Mg concentrated region of the missing portion.
[0011] The Mg concentrated region of the missing portion may further include nickel (Ni), and an amount of magnesium (Mg) included in the Mg concentrated region of the missing portion may be 4.75 to 71.58 parts by mole based on 100 parts by mole of nickel (Ni) in the Mg concentrated region of the missing portion.
[0012] A molar ratio of magnesium (Mg) included in the Mg concentrated region of the missing portion to magnesium (Mg) included in the interface adjacent region of the dielectric layer may be 1.010 to 13.701.
[0013] Magnesium (Mg) included in the Mg concentrated region of the missing portion may form a second phase with at least one of nickel (Ni) and oxygen (O).
[0014] The amount of magnesium (Mg) included in the interface adjacent region of the dielectric layer may be 0.8 atomic % to 4.2 atomic % based on the total amount of components of the interface adjacent region.
[0015] The interface adjacent region of the dielectric layer may also include barium (Ba), titanium (Ti), nickel (Ni), dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), aluminum (Al), silicon (Si), tin (Sn), oxygen (O), or a combination thereof.
[0016] The interface adjacent region of the dielectric layer may include titanium (Ti), and an amount of magnesium (Mg) included in the interface adjacent region of the dielectric layer may be 5.0 to 29.7 parts by mole based on 100 parts by mole of titanium (Ti) in the interface adjacent region of the dielectric layer.
[0017] Another aspect of the present disclosure provides a method for manufacturing a multilayer ceramic capacitor, the method comprising: preparing a dielectric slurry by mixing a barium titanate-based main component powder and a secondary component powder including a magnesium (Mg)-containing compound; manufacturing a dielectric green sheet by using the dielectric slurry, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet laminate by stacking the dielectric green sheets having the conductive paste layer formed thereon; manufacturing a capacitor body including a dielectric layer and an inner electrode layer by firing the dielectric green sheet laminate; and forming an outer electrode on the capacitor body. The capacitor body includes at least one missing portion, the missing portion is defined as a region where the continuity of the inner electrode layer is broken, and the missing portion includes a Mg concentrated region, the Mg concentrated region includes magnesium (Mg) as a main element, the dielectric layer includes an interface adjacent region, the interface adjacent region is defined as a region from an interface between the dielectric layer and the inner electrode layer to a position at a depth of 80nm to 100nm in the dielectric layer, and the interface adjacent region includes magnesium (Mg), and the atomic percentage content of magnesium (Mg) included in the interface adjacent region of the dielectric layer is lower than the atomic percentage content of magnesium (Mg) included in the Mg concentrated region of the missing portion.
[0018] The magnesium (Mg)-containing compound may be mixed in an amount of 0.01 parts by mole to 3 parts by mole based on 100 parts by mole of the barium titanate-based main component powder.
[0019] The secondary component powder may further include a dysprosium (Dy)-containing compound, a terbium (Tb)-containing compound, a manganese (Mn)-containing compound, a vanadium (V)-containing compound, an aluminum (Al)-containing compound, a silicon (Si)-containing compound, a tin (Sn)-containing compound, or a combination thereof.
[0020] Based on 100 parts by mole of the barium titanate-based main component powder, the amount of the dysprosium (Dy)-containing compound can be 0.01 parts by mole to 5 parts by mole, the amount of the terbium (Tb)-containing compound can be 0.01 parts by mole to 5 parts by mole, the amount of the manganese (Mn)-containing compound can be 0.01 parts by mole to 5 parts by mole, the amount of the vanadium (V)-containing compound can be 0.01 parts by mole to 5 parts by mole, the amount of the aluminum (Al)-containing compound can be 0.01 parts by mole to 5 parts by mole, the amount of the silicon (Si)-containing compound can be 0.01 parts by mole to 5 parts by mole, and the amount of the tin (Sn)-containing compound can be 0.01 parts by mole to 5 parts by mole.
[0021] The conductive paste layer may be made of a conductive paste including nickel (Ni).
[0022] Another aspect of the present disclosure provides a method for manufacturing a multilayer ceramic capacitor, the method comprising: preparing a dielectric slurry by mixing a barium titanate-based main component powder and a secondary component powder including a magnesium (Mg)-containing compound; manufacturing a dielectric green sheet by using the dielectric slurry, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet laminate by laminating the dielectric green sheets on which the conductive paste layer is formed; manufacturing a capacitor body including a dielectric layer and an inner electrode layer by firing the dielectric green sheet laminate; and forming an outer electrode on the capacitor body. The firing temperature is 1150° C. to 1250° C. and the hydrogen (H2) content is 0.8% or less. 2 ) concentration and firing the dielectric green sheet stack.
[0023] According to the present disclosure, a multilayer ceramic capacitor may have improved accelerated lifetime reliability due to an increase in a barrier height at an interface of a dielectric layer and an internal electrode layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 A perspective view of a multilayer ceramic capacitor according to an embodiment is shown.
[0025] Figure 2 shows the multilayer ceramic capacitor relative to Figure 1 Cross-sectional view along line II'.
[0026] Figure 3 shows the multilayer ceramic capacitor relative to Figure 1 Cross-sectional view along line II-II'.
[0027] Figure 4 Shows Figure 2 Schematic diagram of a portion of the effective area A in .
[0028] Figure 5A A transmission electron microscope-energy dispersive spectroscopy (TEM-EDS) analysis image of an active region of the multilayer ceramic capacitor according to Example 1 is shown.
[0029] Figure 5B A TEM-EDS analysis image of an active region of the multilayer ceramic capacitor according to Comparative Example 1 is shown.
[0030] Figure 6 An EDS line scan analysis graph near the interface of the dielectric layer and the internal electrode layer of the multilayer ceramic capacitor according to Example 1 is shown.
[0031] Figure 7 A graph showing accelerated lifetime reliability of the multilayer ceramic capacitor according to Example 1 is shown.
[0032] Figure 8A graph showing accelerated lifetime reliability of the multilayer ceramic capacitor according to Comparative Example 1 is shown. DETAILED DESCRIPTION
[0033] Hereinafter, the present disclosure will be described more fully with reference to the accompanying drawings, in which embodiments of the present disclosure are shown. The drawings and description are to be considered illustrative rather than restrictive in nature. Throughout the specification, the same reference numerals represent the same elements. Some constituent elements are enlarged, omitted or briefly shown in the drawings, and the sizes of the corresponding constituent elements do not reflect the actual sizes.
[0034] The accompanying drawings are provided only to allow easy understanding of the embodiments disclosed in this specification and should not be interpreted as limiting the spirit disclosed in this specification. It should be understood that the present disclosure includes all modifications, equivalents, and replacements without departing from the scope and spirit of the present disclosure.
[0035] Terms including ordinal numbers such as "first", "second", etc. will only be used to describe various constituent elements and should not be construed as limiting these constituent elements. These terms are only used to distinguish one constituent element from other constituent elements.
[0036] It should be understood that when an element such as a layer, film, region, or substrate is referred to as being "on" another element, the element may be directly on the other element, or there may be intervening elements. In contrast, when an element is referred to as being "directly on" another element, there are no intervening elements. The terms "on..." or "above..." mean being "on" or "below" a target portion, and do not necessarily mean being on the upper side of a target portion based on the direction of gravity.
[0037] It should be understood that the terms "include", "comprising", "having" or "configuration" indicate the presence of the features, quantities, steps, operations, constituent elements, parts or combinations thereof described in the specification, but do not exclude the possibility of pre-existing or adding one or more other features, quantities, steps, operations, constituent elements, parts or combinations thereof. Unless explicitly described to the contrary, the word "include" and variations such as "include" or "having" will be understood to imply the inclusion of the elements but not the exclusion of any other elements.
[0038] The phrase “in a plan view” or “on a plane” means observing a target portion from the top, and the phrase “in a cross-sectional view” or “on a cross section” means observing a cross section formed by vertically cutting the target portion from the side.
[0039] Throughout the specification, when a part is described as being “connected” to another part, the part may be “directly connected” to the other part, may be “connected” to the other part through a third part, or may be physically or electrically connected to the other part, and corresponding parts that are substantially integrated into one body may be connected to each other and may be represented by different names according to position or function.
[0040] Now refer to Figures 1 to 4 A multilayer ceramic capacitor according to an embodiment is described.
[0041] Figure 1 shows a perspective view of a multilayer ceramic capacitor according to an embodiment, Figure 2 shows the multilayer ceramic capacitor relative to Figure 1 A cross-sectional view of line I-I', Figure 3 shows the multilayer ceramic capacitor relative to Figure 1 A cross-sectional view of line II-II', and Figure 4 Shows Figure 2 Schematic diagram of a portion of the effective area A in .
[0042] Figures 1 to 4 The L-axis direction, W-axis direction, and T-axis direction shown in the figure represent the length direction, width direction, and thickness direction of the capacitor body 110, respectively. Here, the thickness direction (T-axis direction) may be a direction perpendicular to the wide surface (main surface) of the sheet-like constituent element, and may be used as the same concept as the stacking direction of the stacked dielectric layer 111, for example. The length direction (L-axis direction) may be a direction extending parallel to the wide surface (main surface) of the sheet-like constituent element and approximately perpendicular to the thickness direction (T-axis direction), for example, the length direction (L-axis direction) may be a direction in which the first external electrode 131 and the second external electrode 132 are opposite to each other. The width direction (W-axis direction) may be a direction extending parallel to the wide surface (main surface) of the sheet-like constituent element and approximately perpendicular to the thickness direction (T-axis direction) and the length direction (L-axis direction), and the length of the sheet-like constituent element in the length direction (L-axis direction) may be greater than the length in the width direction (W-axis direction).
[0043] Reference Figures 1 to 4 , the multilayer ceramic capacitor 100 according to the embodiment includes a capacitor body 110 and external electrodes 131 and 132 disposed outside the capacitor body 110. The external electrodes 131 and 132 may include a first external electrode 131 and a second external electrode 132 disposed at respective ends of the capacitor body 110 opposite in the length direction (L-axis direction).
[0044] Capacitor body
[0045] As an example, the capacitor body 110 may have an approximately hexahedral shape.
[0046] For better understanding and ease of description of the embodiments, the corresponding sides of the capacitor body 110 opposite to each other in the thickness direction (T-axis direction) will be defined as the first side and the second side, the corresponding sides connected to the first side and the second side and opposite to each other in the length direction (L-axis direction) will be defined as the third side and the fourth side, and the corresponding sides connected to the first side and the second side, connected to the third side and the fourth side and opposite to each other in the width direction (W-axis direction) will be defined as the fifth side and the sixth side.
[0047] For example, the first side as the lower surface may be a mounting surface. In addition, the first side to the sixth side may be flat, and the embodiment is not limited thereto. For example, the first side to the sixth side may be a curved surface, the central portion of which is convex, and the edges as the boundaries of the corresponding sides may be rounded.
[0048] The shape and size of the capacitor body 110 and the number of stacked dielectric layers 111 are not limited to those shown in the drawings of the present embodiment.
[0049] The capacitor body 110 includes a dielectric layer 111 and internal electrode layers 121 and 122. Specifically, the capacitor body 110 includes a dielectric layer 111 and first and second internal electrode layers 121 and 122, the first and second internal electrode layers 121 and 122 are alternately arranged in the thickness direction (T-axis direction), and the dielectric layer 111 is interposed between the first and second internal electrode layers 121 and 122.
[0050] At this time, the adjacent dielectric layers 111 of the capacitor body 110 may be integrated to such an extent that it is difficult to distinguish the boundaries between the adjacent dielectric layers 111 without using a scanning electron microscope (SEM).
[0051] The capacitor body 110 may include an active region A. The active region A contributes to forming the capacity of the multilayer ceramic capacitor 100. For example, the active region A may be a region where the first and second internal electrode layers 121 and 122 stacked in the thickness direction (T-axis direction) overlap.
[0052] The capacitor body 110 may also include a cover region and a side edge region.
[0053] The cover region may be a thickness direction edge and may be disposed in the thickness direction (T-axis direction) on the upper and lower surfaces of the active region A. The cover region may be a single dielectric layer 111 or two or more dielectric layers 111 stacked on the upper and lower surfaces of the active region A, respectively.
[0054] The side edge regions may be width-direction edges, and may be respectively disposed on one side and the other side of the effective region in the width direction (W-axis direction). The side edge regions may be formed by coating a conductive paste layer in a predetermined region on the surface of a dielectric green sheet, laminating the dielectric green sheets on which the conductive paste layer is coated to obtain a dielectric green sheet laminate, laminating dielectric green sheets on which the conductive paste layer is not coated on the corresponding sides of the dielectric green sheet laminate, and performing firing.
[0055] The cover region and the side edge region serve to prevent damage to the first and second internal electrode layers 121 and 122 due to physical stress or chemical stress.
[0056] The first inner electrode layer 121 and the second inner electrode layer 122 may have different polarities and may be alternately arranged to be opposite to each other in the T-axis direction, and the dielectric layer 111 is interposed between the first inner electrode layer 121 and the second inner electrode layer 122, and one end of the first inner electrode layer 121 and one end of the second inner electrode layer 122 may be exposed through the third side and the fourth side of the capacitor body 110, respectively.
[0057] The first and second internal electrode layers 121 and 122 may be electrically insulated from each other by the dielectric layer 111 disposed therebetween.
[0058] The ends of the first inner electrode layer 121 and the ends of the second inner electrode layer 122 alternately exposed through the third side and the fourth side of the capacitor body 110 can be connected to the first outer electrode 131 and the second outer electrode 132, respectively, and the ends of the first inner electrode layer 121 can therefore be electrically connected to each other, and the ends of the second inner electrode layer 122 can therefore be electrically connected to each other.
[0059] The first and second internal electrode layers 121 and 122 include a conductive metal, for example, the first and second internal electrode layers 121 and 122 may include a metal such as Ni, Cu, Ag, Pd, and Au, or an alloy thereof such as an Ag—Pd alloy.
[0060] In addition, the first and second internal electrode layers 121 and 122 may include dielectric particles having the same composition as the ceramic material included in the dielectric layer 111 .
[0061] The first and second internal electrode layers 121 and 122 may be formed using a conductive paste including a conductive metal. A method for printing the conductive paste may include screen printing or gravure printing.
[0062] Reference Figure 4According to the embodiment, the inner electrode layers 121 and 122 include at least one missing portion LP, and the missing portion LP is defined as a region where the continuity of the inner electrode layer is missing. For example, in one inner electrode layer, the missing portions LP may be two or more, for example, 2 to 300, or for example, 2 to 180. For example, with respect to the LT cross section (length direction-thickness direction cross section), the number of missing portions LP may be 2 to 300, and with respect to the WT cross section (width direction-thickness direction cross section), the number of missing portions LP may be 2 to 180.
[0063] The capacitor body 110 may be formed by firing a laminate in which a dielectric layer and an inner electrode layer are stacked in a thickness direction (T-axis direction). At this time, since the metal-based inner electrode layer is fired at a relatively low temperature compared to the dielectric layer including a ceramic material, the inner electrode layer may be over-fired and may be over-contracted when firing the dielectric layer, thereby causing cracks. Therefore, the inner electrode layers 121 and 122 have disconnected portions, i.e., missing portions LP.
[0064] The missing portion LP includes a Mg concentrated region C containing magnesium (Mg) as a main element. Specifically, the missing portion LP may include nickel (Ni) used as a main element when forming the inner electrode layers 121 and 122 and various components generated due to the movement and diffusion of the main components and the secondary components used when forming the dielectric layer 111. The missing portion LP includes a Mg concentrated region C containing magnesium (Mg) as a main element. The Mg concentrated region C may be a region where the concentration of the Mg element is increased in the missing portion LP. In addition, the Mg concentrated region C may be a region where the Mg concentration is higher than that of the region surrounding the Mg concentrated region in the missing portion LP.
[0065] According to the embodiment, when the Mg concentrated region C exists in the missing portion LP of the inner electrode layers 121 and 122, the Mg concentration in the dielectric layer 111 is reduced at the interface between the dielectric layer 111 and the inner electrode layers 121 and 122, so that the Mg element can be suppressed from being excessively used as an acceptor in the dielectric material. In addition, when the oxygen vacancy concentration is reduced due to the suppression of excessive use of Mg in the dielectric layer 111, the barrier height at the interface between the dielectric layer 111 and the inner electrode layers 121 and 122 is increased, so that the accelerated lifetime reliability can be improved.
[0066] In detail, the Mg concentrated region C may include 1.6 atomic % to 11.1 atomic % of magnesium (Mg), for example, 2.0 atomic % to 10.0 atomic % of magnesium (Mg) relative to the total amount of the components present in the Mg concentrated region C. When the missing portion of the inner electrode layer has the Mg concentrated region C where magnesium (Mg) exists in this concentration range, the accelerated lifetime reliability may be improved due to an increase in a barrier height at an interface between the dielectric layer and the inner electrode layer.
[0067] In addition, the Mg concentrated region C of the missing portion LP may further include barium (Ba), titanium (Ti), nickel (Ni), dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), aluminum (Al), silicon (Si), tin (Sn), oxygen (O), or a combination thereof. Here, barium (Ba) and titanium (Ti) may be derived from a main component material used when forming the dielectric layer 111, and may move and diffuse to the missing portion LP of the inner electrode layers 121 and 122. In addition, dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), aluminum (Al), silicon (Si), and tin (Sn) may be derived from a secondary component material used to form the dielectric layer 111, and they may move and diffuse to the missing portion LP of the inner electrode layers 121 and 122. Nickel (Ni) may be derived from a main element material used to form the inner electrode layers 121 and 122.
[0068] For example, the Mg concentrated region C of the missing portion LP may include magnesium (Mg) and titanium (Ti). In this case, the amount of magnesium (Mg) included in the Mg concentrated region C may be 12.68 mol parts or more based on 100 mol parts of titanium (Ti) included in the Mg concentrated region C, for example, the amount of magnesium (Mg) included in the Mg concentrated region C may be 12.68 mol parts to 22000 mol parts or 15 mol parts to 20000 mol parts. When magnesium (Mg) within this content range is included in the Mg concentrated region C, excellent accelerated lifetime reliability may be achieved due to an increase in a barrier height at an interface between a dielectric layer and an inner electrode layer.
[0069] For another example, the Mg concentrated region C of the missing portion LP may include magnesium (Mg) and nickel (Ni). In this case, the amount of magnesium (Mg) included in the Mg concentrated region C may be 4.75 to 71.58 parts by mole based on 100 parts by mole of nickel (Ni) included in the Mg concentrated region C, for example, the amount of magnesium (Mg) included in the Mg concentrated region C may be 5.0 to 60.0 parts by mole. When magnesium (Mg) within this content range is included in the Mg concentrated region C, excellent accelerated lifetime reliability may be achieved due to an increase in a barrier height at an interface between a dielectric layer and an inner electrode layer.
[0070] The molar ratio of magnesium (Mg) included in the Mg concentration region C of the missing portion LP to the magnesium (Mg) included in the interface adjacent region R of the dielectric layer 111 may be 1.010 to 13.701, for example, the molar ratio of magnesium (Mg) included in the Mg concentration region C of the missing portion LP to the magnesium (Mg) included in the interface adjacent region R of the dielectric layer 111 may be 1.1 to 11.0. When the molar ratio of magnesium (Mg) in the Mg concentration region C and the interface adjacent region R is within this range, since the excessive use of the Mg element as an acceptor in the dielectric layer 111 can be suppressed, the oxygen vacancy concentration is reduced. Therefore, the barrier height at the interface of the dielectric layer 111 and the internal electrode layers 121 and 122 is increased, and the accelerated lifetime reliability can be improved accordingly.
[0071] The magnesium (Mg) included in the Mg concentrated region C of the missing portion LP may form a second phase by combining with at least one of nickel (Ni) and oxygen (O). When the magnesium (Mg) exists in the form of a second phase with at least one of nickel (Ni) and oxygen (O), the Mg concentration in the dielectric layer 111 at the interface of the dielectric layer 111 with the internal electrode layers 121 and 122 is reduced, thereby suppressing the Mg element from excessively serving as an acceptor in the dielectric layer 111.
[0072] The average thickness of the first internal electrode layer 121 and the second internal electrode layer 122 may be 0.1 μm to 2 μm. The average thickness of the first internal electrode layer 121 and the second internal electrode layer 122 may be measured in the following manner: in a scanning electron microscope (SEM) image of the measured cross-sectional sample as described above, the center point of the first internal electrode layer 121 or the second internal electrode layer 122 in the length direction (L-axis direction) or the width direction (W-axis direction) is set as a reference point, and the thickness of the first internal electrode layer 121 or the second internal electrode layer 122 is measured at ten points spaced apart from the reference point at a predetermined interval, and their arithmetic mean is calculated. The interval between the ten points may be adjusted according to the scale of the scanning electron microscope (SEM) image, for example, may be 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm. At this time, all ten points must be set in the first internal electrode layer 121 or the second internal electrode layer 122, and when all ten points are not set in the first internal electrode layer 121 or the second internal electrode layer 122, the position of the reference point can be changed or the interval between the ten points can be adjusted.
[0073] The dielectric layer 111 may include a barium titanate-based main component including barium (Ba) and titanium (Ti).
[0074] The barium titanate-based main component is a dielectric matrix material, has a high dielectric constant, and contributes to forming the dielectric constant of the multilayer ceramic capacitor 100 .
[0075] For example, the barium titanate-based main component may include BaTiO 3 、Ba(Ti,Zr)O 3 、Ba(Ti,Sn)O 3 、(Ba,Ca)TiO 3 、(Ba,Ca)(Ti,Zr)O 3 、(Ba,Ca)(Ti,Sn)O 3 、(Ba,Sr)TiO 3 、(Ba,Sr)(Ti,Zr)O 3 、(Ba,Sr)(Ti,Sn)O 3 or a combination thereof.
[0076] The dielectric layer 111 may further include a secondary component including magnesium (Mg). For example, in addition to magnesium (Mg), the secondary component may further include dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), aluminum (Al), silicon (Si), tin (Sn), or a combination thereof, but is not limited thereto.
[0077] The dielectric layer 111 may include an interface adjacent region R defined as a region from an interface of the dielectric layer 111 and the internal electrode layers 121 and 122 to a position at a depth of 80 nm to 100 nm in the dielectric layer 111. For example, the interface adjacent region R may be disposed near the Mg concentrated region C of the missing portion LP.
[0078] The interface adjacent region R of the dielectric layer 111 includes magnesium (Mg).
[0079] The atomic percentage content of magnesium (Mg) included in the interface adjacent region R of the dielectric layer 111 may be lower than the atomic percentage content of magnesium (Mg) included in the Mg concentrated region C of the missing portion LP. This is because: as the Mg concentrated region C of the missing portion LP is formed, the Mg concentration in the dielectric layer 111 is reduced in the interface adjacent region R of the dielectric layer 111 disposed near the Mg concentrated region C. Therefore, when the atomic percentage content of magnesium (Mg) included in the interface adjacent region R is lower than the atomic percentage content of magnesium (Mg) included in the Mg concentrated region C, the phenomenon that the Mg element is excessively used as an acceptor in the dielectric layer 111 can be suppressed. In addition, the reduction in the oxygen vacancy concentration caused by suppressing the excessive use of Mg in the dielectric layer 111 leads to an increase in the barrier height at the interface of the dielectric layer 111 and the internal electrode layers 121 and 122, thereby improving the accelerated lifetime reliability.
[0080] The interface adjacent region R may include 0.8 atomic % to 4.2 atomic % of magnesium (Mg), for example, 1.0 atomic % to 3.5 atomic % of magnesium (Mg), based on the total amount of components present in the interface adjacent region R of the dielectric layer 111. This is because: based on the formation of the Mg concentrated region C in the missing portion LP of the inner electrode layers 121 and 122, the Mg concentration in the dielectric layer 111 is reduced in the interface adjacent region R of the dielectric layer 111 disposed near the Mg concentrated region C. Therefore, when the magnesium (Mg) in the interface adjacent region R has this content range, the phenomenon that the Mg element in the dielectric layer 111 excessively serves as an acceptor can be suppressed, and the barrier height at the interface is increased, thereby improving the accelerated lifetime reliability.
[0081] The interface adjacent region R of the dielectric layer 111 may further include barium (Ba), titanium (Ti), nickel (Ni), dysprosium (Dy), terbium (Tb), manganese (Mn), vanadium (V), aluminum (Al), silicon (Si), tin (Sn), oxygen (O), or a combination thereof. The sources of the components correspond to the description about the components included in the Mg concentrated region C of the missing portion LP.
[0082] For example, the interface adjacent region R of the dielectric layer 111 may include magnesium (Mg) and titanium (Ti). In this case, the amount of magnesium (Mg) included in the interface adjacent region R may be 5.0 to 29.7 parts by mole based on 100 parts by mole of titanium (Ti) included in the interface adjacent region R, for example, the amount of magnesium (Mg) included in the interface adjacent region R may be 8.0 to 25.0 parts by mole. When magnesium (Mg) within this content range is included in the interface adjacent region R, the barrier height at the interface of the dielectric layer and the inner electrode layer is increased, thereby having excellent accelerated lifetime reliability.
[0083] The average thickness (average length in the T-axis direction) of the dielectric layer 111 may be 0.2 μm to 8.0 μm, for example, 2.4 μm to 7.8 μm. When the average thickness of the dielectric layer 111 is within this range, the reliability of the multilayer ceramic capacitor is excellent. The average thickness of the dielectric layer 111 may be measured in the following manner: in a scanning electron microscope (SEM) image of the measured cross-sectional sample as described above, the center point of the dielectric layer 111 in the length direction (L-axis direction) or the width direction (W-axis direction) is set as a reference point, and the thickness of the dielectric layer 111 is measured at ten points spaced apart from the reference point at predetermined intervals, and their arithmetic mean is calculated. The intervals between the ten points may be adjusted according to the scale of the scanning electron microscope (SEM) image, for example, may be 1 μm to 100 μm, 1 μm to 50 μm, or 1 μm to 10 μm. At this time, the ten points must all be disposed in the dielectric layer 111 , and when the ten points are not all disposed in the dielectric layer 111 , the positions of the reference points may be changed or the intervals between the ten points may be adjusted.
[0084] For reference, given Figure 4 To help understand the missing portion LP, the Mg concentrated region C, and the interface adjacent region R, and for ease of description, the missing portion LP, the Mg concentrated region C, and the interface adjacent region R are shown in some drawings, and the drawings are not limited thereto. That is, the region where the continuity is broken in the inner electrode layers 121 and 122 may be the missing portion LP, the region including the Mg element as the main element in the missing portion LP or the region where the Mg element concentration is increased may be the Mg concentrated region C, and the interface adjacent region R may be set at any position where the interface between the dielectric layer 111 and the inner electrode layers 121 and 122 is located, and may be set on other sides in addition to one side of one inner electrode layer.
[0085] According to an embodiment, the Mg element and the Mg content present in the Mg concentrated region C formed on the missing portion LP of the inner electrode layers 121 and 122 and the interface adjacent region R of the dielectric layer 111 may be determined through transmission electron microscopy-energy dispersive spectrometer (TEM-EDS) analysis.
[0086] In detail, the multilayer ceramic capacitor 100 may be placed in an epoxy resin mixed solution for curing, the surface (LT surface) of the capacitor body 110 in the L-axis direction and the T-axis direction may be polished to 1 / 2 depth in the W-axis direction, the capacitor body 110 may be fixed, the capacitor body 110 may be kept in a vacuum atmosphere chamber, and a cross-sectional sample of the capacitor body 110 may be obtained to observe the effective area A where the dielectric layer 111 overlaps the internal electrode layers 121 and 122. The effective area A (e.g., the upper part, the central part, and the side part of the effective area) of the cross-sectional sample may be measured using a transmission electron microscope (TEM). Specifically, the transmission electron microscope may be used to measure using a focused ion beam (Xe-FIB) under conditions of an acceleration voltage of 200 kV and a magnification of 110k times, so that at least one layer (e.g., three to one hundred layers or five to fifty layers) of the corresponding dielectric layer 111 and the internal electrode layers 121 and 122 may be shown. The presence and content of the magnesium (Mg) element may be determined from a transmission electron microscope (TEM) image of a measured cross-sectional sample according to EDS analysis. In detail, the formation of the Mg concentrated region C in the missing portion LP of the inner electrode layers 121 and 122 may be determined, and the content of the magnesium (Mg) element present in the interface adjacent region R of the Mg concentrated region C and the dielectric layer 111 may be determined. The content of the Mg element may be an average value measured at at least one point (e.g., two points, three points, or five points) of the corresponding upper, central, and side portions of the active region.
[0087] External electrode
[0088] The first and second external electrodes 131 and 132 are supplied with voltages of different polarities and may be electrically connected to the exposed portions of the first and second internal electrode layers 121 and 122 , respectively.
[0089] According to the above configuration, when a predetermined voltage is applied to the first external electrode 131 and the second external electrode 132, charges may be accumulated between the first internal electrode layer 121 and the second internal electrode layer 122 facing each other. At this time, the capacitance of the multilayer ceramic capacitor 100 is proportional to the overlapping area of the first internal electrode layer 121 and the second internal electrode layer 122 overlapping each other in the T-axis direction in the active region.
[0090] The first external electrode 131 may include a first connecting portion arranged on the third side of the capacitor body 110 and connected to the first internal electrode layer 121, and a first band portion arranged at a corner where the third side of the capacitor body 110 intersects with the first side and the second side and / or the fifth side and the sixth side, and the second external electrode 132 may include a second connecting portion arranged on the fourth side of the capacitor body 110 and connected to the second internal electrode layer 122, and a second band portion arranged at a corner where the fourth side of the capacitor body 110 intersects with the first side and the second side and / or the fifth side and the sixth side.
[0091] The first band portion may extend from the first connection portion to a portion of the first side and a portion of the second side and / or a portion of the fifth side and a portion of the sixth side of the capacitor body 110, and the second band portion may extend from the second connection portion to a portion of the first side and a portion of the second side and / or a portion of the fifth side and a portion of the sixth side of the capacitor body 110. The first band portion and the second band portion may be used to improve the bonding strength between the first and second external electrodes 131 and 132 and the capacitor body 110.
[0092] Each of the first and second external electrodes 131 and 132 may include a sintered metal layer contacting the capacitor body 110 , a conductive resin layer disposed to cover the sintered metal layer, and a plated layer disposed to cover the conductive resin layer.
[0093] The sintered metal layer may include conductive metal and glass.
[0094] The conductive metal may include copper (Cu), nickel (Ni), silver (Ag), palladium (Pd), gold (Au), platinum (Pt), tin (Sn), tungsten (W), titanium (Ti), lead (Pb), alloys thereof, or combinations thereof, for example, the conductive metal may include copper (Cu) or an alloy of copper (Cu). When the conductive metal includes copper, less than or equal to 5 mol parts of metal other than copper may be included relative to 100 mol parts of copper.
[0095] The glass may include a composition of mixed oxides, for example, the oxide may be at least one of silicon oxide, boron oxide, aluminum oxide, transition metal oxide, alkali metal oxide and alkaline earth metal oxide. The transition metal may be selected from zinc (Zn), titanium (Ti), copper (Cu), vanadium (V), manganese (Mn), iron (Fe) and nickel (Ni), the alkali metal may be selected from lithium (Li), sodium (Na) and potassium (K), and the alkaline earth metal may be selected from magnesium (Mg), calcium (Ca), strontium (Sr) and barium (Ba).
[0096] Alternatively, the conductive resin layer may be formed on the sintered metal layer, for example, may be formed to completely cover the sintered metal layer. In addition, the first and second external electrodes 131 and 132 may not include the sintered metal layer, and in this case, the conductive resin layer may contact the capacitor body 110 .
[0097] The conductive resin layer may extend to the first and second sides and / or the fifth and sixth sides of the capacitor body 110, so that the length of the region (i.e., the band portion) where the conductive resin layer extends to the first and second sides and / or the fifth and sixth sides of the capacitor body 110 may be longer than the length of the region (i.e., the band portion) where the sintered metal layer extends to the first and second sides and / or the fifth and sixth sides of the capacitor body 110. In other words, the conductive resin layer may be formed on the sintered metal layer and may cover the sintered metal layer.
[0098] The conductive resin layer includes resin and conductive metal.
[0099] There is no particular limitation on the resin included in the conductive resin layer as long as it has bonding and impact absorbing properties and is mixed with conductive metal powder to make a paste. For example, the resin included in the conductive resin layer may include phenolic resin, acrylic resin, silicone resin, epoxy resin or polyimide resin.
[0100] The conductive metal included in the conductive resin layer serves to electrically connect with the first and second internal electrode layers 121 and 122 or the sintered metal layer.
[0101] The conductive metal included in the conductive resin layer may have a spherical shape, a flake shape, or a combination thereof. That is, the conductive metal may be made into a flake shape, a spherical shape, or a mixed shape of the flake shape and the spherical shape.
[0102] Here, the spherical shape may include a shape that is not a completely spherical shape, for example, a shape in which the length ratio of the major axis to the minor axis (major axis / minor axis) may be 1.45 or less. The flake-shaped powder may refer to a powder having a flat and elongated shape, and is not particularly limited, for example, the length ratio of the major axis to the minor axis (major axis / minor axis) may be 1.95 or more.
[0103] The first and second external electrodes 131 and 132 may further include a plating layer disposed outside the conductive resin layer.
[0104] The coating may include nickel (Ni), copper (Cu), tin (Sn), palladium (Pd), platinum (Pt), gold (Au), silver (Ag), tungsten (W), titanium (Ti), lead (Pb) or alloys thereof. For example, the coating may be a nickel (Ni) coating or a tin (Sn) coating, and may have a form in which a nickel (Ni) coating and a tin (Sn) coating are stacked in sequence, or may have a form in which a tin (Sn) coating, a nickel (Ni) coating and a tin (Sn) coating are stacked in sequence. In addition, the coating may include one or more nickel (Ni) coatings and / or one or more tin (Sn) coatings.
[0105] The plating layer may improve mountability on a substrate, structural reliability, exterior durability, heat resistance, and equivalent series resistance (ESR) of the multilayer ceramic capacitor 100 .
[0106] A method of manufacturing the multilayer ceramic capacitor 100 according to an embodiment will now be described.
[0107] The method of manufacturing the multilayer ceramic capacitor 100 according to the embodiment may include: mixing a barium titanate-based main component powder and a secondary component powder including a magnesium (Mg)-containing compound to prepare a dielectric slurry; manufacturing a dielectric green sheet using the dielectric slurry, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet laminate by stacking the dielectric green sheets having the conductive paste layer formed thereon; manufacturing a capacitor body including a dielectric layer and an inner electrode layer by firing the dielectric green sheet laminate; and forming an outer electrode on the capacitor body.
[0108] First, a dielectric slurry is prepared by mixing a barium titanate-based main component powder and a secondary component powder including a magnesium (Mg)-containing compound.
[0109] The barium titanate-based main component powder is the same as the barium titanate-based main component included in the dielectric layer, and thus a description thereof will be omitted here.
[0110] Based on 100 molar parts of the barium titanate-based main component powder, a magnesium (Mg) compound can be mixed in an amount of 0.01 to 3 molar parts, for example, a magnesium (Mg) compound can be mixed in an amount of 0.05 to 1.5 molar parts. When the magnesium (Mg) compound is mixed within this content range, a Mg concentration region C can be formed in the missing portion LP of the inner electrode layer, thereby reducing the Mg concentration in the dielectric layer at the interface between the dielectric layer and the inner electrode layer. Therefore, since the phenomenon that the Mg element is excessively used as an acceptor in the dielectric layer is suppressed, the oxygen vacancy concentration is reduced, and the barrier height at the interface between the dielectric layer and the inner electrode layer can be increased, thereby obtaining a multilayer ceramic capacitor with excellent accelerated life reliability.
[0111] The secondary component powder may further include dysprosium (Dy)-containing compounds, terbium (Tb)-containing compounds, manganese (Mn)-containing compounds, vanadium (V)-containing compounds, aluminum (Al)-containing compounds, silicon (Si)-containing compounds, tin (Sn)-containing compounds, or combinations thereof.
[0112] The minor component powder may be an oxide or salt compound, or may be used as a sol dispersed in an organic solvent.
[0113] The amount of the dysprosium (Dy) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, the amount of the terbium (Tb) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, the amount of the manganese (Mn) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, the amount of the vanadium (V) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, The amount of the secondary component powder may be 0.01 to 5 parts by mole, the amount of the aluminum (Al) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, the amount of the silicon (Si) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder, and the amount of the tin (Sn) compound may be 0.01 to 5 parts by mole based on 100 parts by mole of the barium titanate-based main component powder. When the secondary component powder is included within this content range, a multilayer ceramic capacitor having high capacity, high reliability, and excellent withstand voltage characteristics may be obtained.
[0114] The dielectric slurry may also be prepared by further mixing additives such as a dispersant, a binder, a plasticizer, a lubricant, and an antistatic agent and a solvent.
[0115] For example, the dispersant may include a phosphate dispersant, a polycarboxylic acid dispersant, or a combination thereof. Based on 100 parts by weight of the barium titanate-based main component powder, the dispersant may be mixed in an amount of 0.1 to 5 parts by weight (e.g., 0.3 to 3 parts by weight). When the dispersant is mixed within this content range, the dispersibility of the dielectric slurry may be excellent, and the amount of impurities contained in the manufactured dielectric layer may be reduced.
[0116] For example, the binder may be an acrylic resin, a polyvinyl butyl resin, a polyvinyl acetal resin, an ethyl cellulose resin, etc. The binder may be mixed in an amount of 0.1 to 50 parts by weight (e.g., 3 to 30 parts by weight) based on 100 parts by weight of the barium titanate-based main component powder. When the binder is mixed within this content range, the dispersibility of the dielectric slurry may be excellent, and the amount of impurities contained in the manufactured dielectric layer may be reduced.
[0117] For example, the plasticizer may include: phthalic acid compounds such as dioctyl phthalate, butyl benzyl phthalate, dibutyl phthalate, dihexyl phthalate, di(2-ethylhexyl) phthalate, or di(2-ethylbutyl) phthalate; adipic acid compounds such as dihexyl adipate or di(2-ethylhexyl) adipate; glycol compounds such as ethylene glycol, diethylene glycol, and triethylene glycol; and glycol ester compounds such as triethylene glycol dibutyrate, triethylene glycol di(2-ethylbutyrate), or triethylene glycol di(2-ethylhexanoate), etc. The plasticizer may be mixed in an amount of 0.1 to 20 parts by weight (e.g., 1 to 10 parts by weight) based on 100 parts by weight of the barium titanate-based main component powder. When the plasticizer is mixed within this content range, dispersibility of the dielectric slurry may be excellent, and the amount of impurities included in the manufactured dielectric layer may be reduced.
[0118] The solvent may be an aqueous solvent such as water; an alcohol solvent such as ethanol, methanol, benzyl alcohol and methoxyethanol; a glycol solvent such as ethylene glycol and diethylene glycol; a ketone solvent such as acetone, methyl ethyl ketone, methyl isobutyl ketone and cyclohexanone; an ester solvent such as butyl acetate, ethyl acetate, carbitol acetate or carbitol acetate butyl ester; an ether solvent such as methyl cellosolve, ethyl cellosolve, butyl ether or tetrahydrofuran; and an aromatic solvent such as benzene, toluene or xylene. Considering the solubility or dispersibility of various additives included in the dielectric slurry, the solvent may be an alcohol solvent or an aromatic solvent. Based on 100 parts by weight of the barium titanate-based main component powder, the solvent may be mixed in an amount of 50 parts by weight to 1000 parts by weight (e.g., 100 parts by weight to 500 parts by weight). When the solvent is mixed within this content range, the dielectric slurry components may be fully mixed, and the solvent may be easily removed thereafter.
[0119] The barium titanate-based main component powder and the secondary component powder may be mixed using a wet ball mill or a stirring mill. When zirconia balls are used in a wet ball mill, zirconia balls having a diameter of 0.1 to 10 mm may be used for wet mixing for 8 to 48 hours or 10 to 24 hours.
[0120] The prepared dielectric slurry forms a dielectric layer when fired.
[0121] A method for forming the prepared dielectric slurry into a sheet may include a tape forming method such as a doctor blade method and a casting roll method, for example, a manifold discharge type roll-on forming coater may be used, and a dielectric green sheet may be obtained by drying the formed body.
[0122] In order to form a conductive paste layer that becomes an inner electrode layer after firing, a conductive paste can be prepared by mixing a conductive powder made of a conductive metal or an alloy thereof, a binder, and a solvent. If necessary, barium titanate powder can be mixed together as a co-material. The co-material can inhibit the sintering of the conductive powder during the firing process. The conductive paste is applied to the surface of the dielectric green sheet in a predetermined pattern using various printing methods (such as screen printing) or transfer methods to form a conductive paste layer.
[0123] The conductive powder may include nickel (Ni) or an alloy of nickel (Ni).
[0124] The dielectric green sheet laminate is manufactured by laminating a plurality of dielectric green sheets on which internal electrode patterns have been formed and then pressing them in a laminating direction. At this time, a plurality of dielectric green sheets on which internal electrode patterns are not formed may be laminated on the upper and lower surfaces of the dielectric green sheet laminate in the laminating direction to form a cover region.
[0125] Alternatively, a process for cutting the manufactured dielectric green sheet laminate into a predetermined size by dicing or the like may be performed.
[0126] In addition, as required, the dielectric green sheet stack may be cured and dried to remove plasticizers and the like, and after curing and drying, drum polishing may be performed by using a horizontal centrifugal drum device. Regarding drum polishing, the dielectric green sheet stack is placed in a drum container together with a medium and a polishing liquid, and unnecessary parts (such as burrs generated during cutting) may be removed by applying rotation or vibration to the drum container. In addition, after drum polishing, the dielectric green sheet stack may be washed with a cleaning solution such as water and dried.
[0127] The capacitor body can be manufactured by removing the binder and firing the dielectric green sheet laminate.
[0128] The binder removal treatment conditions may be appropriately adjusted according to the components of the dielectric layer or the inner electrode layer. For example, the temperature rise rate during the binder removal may be 5° C. / hour to 300° C. / hour, the carrier temperature may be 180° C. to 400° C., and the temperature holding time may be 0.5 hour to 24 hours. The atmosphere during the binder removal process may be air or a reducing atmosphere.
[0129] The conditions of the firing process may be appropriately adjusted according to the main component composition of the dielectric layer or the main component composition of the inner electrode. For example, the firing may be performed at a temperature of 1100° C. to 1400° C. (e.g., 1200° C. to 1350° C.). In addition, the firing may be performed for 0.5 hours to 8 hours (e.g., 1 hour to 3 hours). The firing may also be performed in a reducing atmosphere (e.g., an atmosphere in which a mixed gas of nitrogen and hydrogen is humidified). When the inner electrode includes nickel (Ni) or a nickel (Ni) alloy, the oxygen partial pressure in the firing atmosphere may be 1.0×10 -14MPa to 1.0×10 -10 MPa.
[0130] After the firing process, annealing may be performed as needed. Annealing is a process for reoxidizing the dielectric layer, and annealing may be performed when firing is performed in a reducing atmosphere. The conditions of the annealing process may also be appropriately adjusted according to the composition of the dielectric layer. For example, the temperature during annealing may be 950° C. to 1150° C., the time may be 0 hours to 20 hours, and the temperature increase rate may be 50° C. / hour to 500° C. / hour. The annealing atmosphere may be humidified nitrogen (N 2 ) atmosphere, and the oxygen partial pressure can be 1.0×10 -9 MPa to 1.0×10 -5 MPa.
[0131] In the binder removal process, the firing process, or the annealing process, for example, a wetting agent may be used to wet nitrogen or a mixed gas, and in this case, the temperature of the wetting agent may be 5° C. to 75° C. The binder removal process, the firing process, and the annealing process may be performed continuously or independently.
[0132] Optionally, surface treatment (such as a sandblasting process, a laser irradiation process, and a barrel polishing process) may be performed on the third and fourth sides of the manufactured capacitor body 110. By performing the surface treatment, the end of the first inner electrode layer and the end of the second inner electrode layer may be exposed on the third and fourth sides, so that the electrical connectivity between the first outer electrode and the first inner electrode and between the second outer electrode and the second inner electrode may be improved, and an alloy portion may be easily formed.
[0133] External electrodes are formed on the manufactured capacitor body 110 .
[0134] For example, the sintered metal layer may be formed by applying a paste for forming the sintered metal layer and then sintering it.
[0135] The paste for forming the sintered metal layer may include conductive metal and glass. The description of conductive metal and glass is the same as that of the conductive metal and glass described above, so repeated description will be omitted. The paste for forming the sintered metal layer may optionally include a binder, a solvent, a dispersant, a plasticizer, an oxide powder, etc. For example, the binder may use ethyl cellulose, acrylic acid, butyral, etc., and the solvent may use an organic solvent (e.g., terpineol, butyl carbitol, ethanol, methyl ethyl ketone, acetone, toluene, etc.) or an aqueous solvent.
[0136] The method for applying the paste for forming the sintered metal layer to the outer surface of the capacitor body 110 may include a dipping method, various printing methods such as screen printing, a coating method using a dispenser, etc., and a spraying method using a sprayer. The paste for forming the sintered metal layer may be applied to at least the third and fourth sides of the capacitor body 110, and may be optionally applied to portions of the first, second, fifth, and / or sixth sides forming the band portions of the first and second external electrodes.
[0137] The capacitor body 110 coated with the paste for forming the sintered metal layer is dried and then sintered at a temperature of 700° C. to 1000° C. for 0.1 to 3 hours to form a sintered metal layer.
[0138] Alternatively, a paste for forming a conductive resin layer may be applied to the outer surface of the obtained capacitor body 110 and then may be cured to form the conductive resin layer.
[0139] The paste for forming the conductive resin layer may include resin, and may optionally include conductive metal or non-conductive filler. The description of conductive metal and resin is the same as the description of the conductive metal and resin mentioned above, so repeated description will be omitted. The paste for forming the conductive resin layer may optionally include adhesive, solvent, dispersant, plasticizer, oxide powder, etc. For example, adhesive may use ethyl cellulose, acrylic acid and butyral, and solvent may use organic solvent (such as terpineol, butyl carbitol, ethanol, methyl ethyl ketone, acetone and toluene) or aqueous solvent.
[0140] For example, the conductive resin layer may be formed by immersing the capacitor body 110 in a paste for forming the conductive resin layer and curing it, printing the paste for forming the conductive resin layer on the surface of the capacitor body 110 by screen printing or gravure printing and curing it, or applying the paste for forming the conductive resin layer to the surface of the capacitor body 110 and curing it.
[0141] A plating layer is formed on the outer side of the conductive resin layer.
[0142] For example, the plated layer may be formed by a plating method, or may be formed by sputtering or electrodeposition.
[0143] The above implementation examples will be described in more detail by the following examples. However, the following examples are only for illustrative purposes and are not intended to limit the scope.
[0144] (Manufacturing of multilayer ceramic capacitors)
[0145] Example 1 and Comparative Example 1
[0146] The dielectric slurry was prepared by mixing barium titanate (BaTiO 3) and 1.5 mol parts of magnesium oxide (MgO) and 3 mol parts of dysprosium oxide (Dy 2 O 3 ), 1.5 molar parts of terbium oxide (Tb 2 O 3 ), 1 mol of manganese oxide (MnO 2 ), 1 mol of vanadium oxide (V 2 O 5 ), 1 mol of aluminum oxide (Al 2 O 3 ), 3 molar parts of silicon oxide (SiO 2 ) and 1 mol of tin oxide (SnO 2 ) are mixed. The content of each minor component powder is based on 100 parts by mole of the barium titanate major component powder. At this time, mixing is performed in the following manner: using zirconium oxide balls (ZrO 2 The mixture is prepared by mixing with a microsphere (ball) as a dispersion medium, and ethanol / toluene, a wetting and dispersing agent and a polyvinyl butyral (PVB) resin as a binder are added together, followed by mechanical grinding.
[0147] A dielectric green sheet was manufactured from the prepared dielectric slurry using a manifold discharge type roll-on coating machine.
[0148] A conductive paste layer including nickel (Ni) was printed on the surface of the dielectric green sheet, and the dielectric green sheets having the conductive paste layer formed thereon were stacked and compressed to produce a dielectric green sheet stack (length×width×height=3.2 mm×2.5 mm×2.5 mm).
[0149] The manufactured dielectric green sheet laminate was subjected to a plasticizing process at 400° C. or less in a nitrogen atmosphere, and in the case of Example 1, at a firing temperature of 1150° C. to 1250° C. and 0.8% or less of hydrogen (H 2 ) concentration, and in the case of Comparative Example 1, at a firing temperature of 1100° C. to 1140° C. and 0.9% or more of hydrogen (H 2 ) concentration.
[0150] For example, the external electrodes are formed through a plating process, thereby manufacturing a multilayer ceramic capacitor.
[0151] Assessment 1: TEM-EDS analysis
[0152] The multilayer ceramic capacitors manufactured in Example 1 and Comparative Example 1 were subjected to TEM-EDS (transmission electron microscope-energy dispersive spectrometer) analysis, and the results are shown in FIG. Figure 5A and Figure 5B middle.
[0153] The TEM-EDS analysis was performed using the following method. The multilayer ceramic capacitors manufactured according to Example 1 and Comparative Example 1 were placed in an epoxy resin mixed solution and cured, the surface of the capacitor body in the L-axis direction and the T-axis direction (LT surface) was polished to 1 / 2 depth in the W-axis direction, the capacitor body was fixed, and the capacitor body was kept in a vacuum atmosphere chamber to obtain a cross-sectional sample so that the effective area where the dielectric layer and the inner electrode layer overlapped could be observed. The effective area ( Figure 2 Specifically, the measurement was performed using a TEM under the conditions of an acceleration voltage of 200 kV and a magnification of 110 k times using a Xe-FIB (focused ion beam), so that six dielectric layers and six internal electrode layers were visible, respectively.
[0154] In the TEM image of the measured cross-sectional sample, the formation of the Mg concentrated region in the missing portion of the inner electrode layer was confirmed by EDS mapping analysis, and the results are shown in FIG. Figure 5A and Figure 5B middle.
[0155] Figure 5A shows a TEM-EDS analysis image of an active area of a multilayer ceramic capacitor according to Example 1, Figure 5B A TEM-EDS analysis image of an active region of the multilayer ceramic capacitor according to Comparative Example 1 is shown.
[0156] Reference Figure 5A In the case of Example 1 according to the embodiment, it can be found that a Mg concentrated region including Mg element as a main element is formed in the missing portion of the inner electrode layer (i.e., the region where the continuity of the inner electrode layer is destroyed). It can be found that the Mg element exists in the interface adjacent region in the dielectric layer, which is adjacent to the Mg concentrated region and close to the interface between the dielectric layer and the inner electrode layer. At this time, it can be found that the concentration (i.e., atomic percentage content) of the Mg element existing in the interface adjacent region in the dielectric layer is lower than the concentration (i.e., atomic percentage content) of the Mg element existing in the Mg concentrated region of the missing portion of the inner electrode layer.
[0157] On the other hand, refer to Figure 5B In the case of Comparative Example 1 manufactured under firing conditions different from those of Example 1, it can be seen that the Mg concentrated region is not well formed in the missing portion of the internal electrode layer.
[0158] Assessment 2: EDS-Line Scan Analysis
[0159] Energy dispersive fluorescence spectroscopy (EDS) line scan analysis was performed on the multilayer ceramic capacitor manufactured in Example 1, and the results are shown in Figure 6 middle.
[0160] In detail, in the TEM image of the cross-sectional sample measured in Evaluation 1, EDS line scan analysis was performed from the inner electrode layer to the dielectric layer to examine the change in the atomic % concentration of the Mg element in the interface adjacent region and the Mg concentrated region of the dielectric layer, and the results are shown in Figure 6 middle.
[0161] Figure 6 An EDS line scan analysis graph near the interface of the dielectric layer and the internal electrode layer of the multilayer ceramic capacitor according to Example 1 is shown.
[0162] Reference Figure 6 , the region from 0nm to 250nm where the Mg element concentration converges to 0 is a continuous part of the inner electrode layer, the region from 270nm to 400nm where the Mg element concentration increases corresponds to a part of the missing part of the inner electrode layer, and the region from 400nm to 480nm where the Mg element concentration decreases corresponds to the interface adjacent region of the dielectric layer. Thus, it can be confirmed that there is a Mg concentrated region where the Mg element concentration increases in the missing part of the inner electrode layer, and it can be found that in the case of Example 1 according to the embodiment, the concentration of the Mg element is relatively reduced in the interface adjacent region of the dielectric layer. It can be seen that the phenomenon that the Mg element is excessively used as an acceptor in the dielectric material is suppressed at the interface between the dielectric layer and the inner electrode layer, and the barrier height increases accordingly.
[0163] Assessment 3: Accelerated Lifetime Reliability
[0164] The reliability of the following items of the multilayer ceramic capacitors manufactured according to Example 1 and Comparative Example 1 were measured, and the results are shown in Figure 7 and Figure 8 middle.
[0165] MTTF (Mean Time to Failure): After mounting 40 sample pieces on a reliability substrate, the mean time to failure (hours) was obtained by measuring under the conditions of a temperature of 125° C., a voltage of 9.45 V, and 48 hours.
[0166] Figure 7 A graph showing accelerated life reliability of a multilayer ceramic capacitor according to Example 1, Figure 8 A graph showing accelerated lifetime reliability of the multilayer ceramic capacitor according to Comparative Example 1 is shown.
[0167] Reference Figure 7 and Figure 8 In the case of Example 1, in which there is a Mg concentrated area in the missing portion of the inner electrode layer and the concentration of the Mg element is relatively reduced in the interface adjacent area of the dielectric layer, it is found that the accelerated life reliability is better than that of Comparative Example 1.
[0168] While the invention has been described in connection with what are presently considered to be practical embodiments, it should be understood that the invention is not limited to the disclosed embodiments, but on the contrary is intended to cover various modifications and equivalent arrangements included within the spirit and scope of the appended claims.
Claims
1. A multilayer ceramic capacitor comprising: a capacitor body including a dielectric layer and an inner electrode layer; as well as An external electrode is disposed on the capacitor body, wherein the capacitor body includes at least one missing portion, the missing portion being defined as a region where the continuity of the inner electrode layer is broken, and the missing portion includes a Mg concentrated region, the Mg concentrated region including Mg as a main element, The dielectric layer includes an interface adjacent region, the interface adjacent region being defined as a region from an interface between the dielectric layer and the inner electrode layer to a position in the dielectric layer at a depth of 80 nm to 100 nm, and the interface adjacent region includes Mg, and An atomic percentage content of Mg included in the interface adjacent region of the dielectric layer is lower than an atomic percentage content of Mg included in the Mg concentrated region of the missing portion.
2. The multilayer ceramic capacitor according to claim 1, wherein The amount of Mg included in the Mg concentrated region is 1.6 atomic % to 11.1 atomic % based on the total amount of components of the Mg concentrated region of the missing portion.
3. The multilayer ceramic capacitor according to claim 1, wherein The Mg concentrated region of the missing portion further includes Ba, Ti, Ni, Dy, Tb, Mn, V, Al, Si, Sn, O or a combination thereof.
4. The multilayer ceramic capacitor according to claim 3, wherein: The Mg concentrated region of the missing portion also includes Ti, and The amount of Mg included in the Mg concentrated region of the missing portion is 12.68 to 22000 parts by mol based on 100 parts by mol of Ti in the Mg concentrated region of the missing portion.
5. The multilayer ceramic capacitor according to claim 3, wherein: The Mg concentrated region of the missing portion also includes Ni, and The amount of Mg included in the Mg concentrated region of the missing portion is 4.75 to 71.58 parts by mol based on 100 parts by mol of Ni in the Mg concentrated region of the missing portion.
6. The multilayer ceramic capacitor according to claim 1, wherein A molar ratio of Mg included in the Mg concentrated region of the missing portion to Mg included in the interface adjacent region of the dielectric layer is 1.010 to 13.
701.
7. The multilayer ceramic capacitor according to claim 1, wherein: Mg included in the Mg concentrated region of the missing portion forms a second phase with at least one of Ni and O.
8. The multilayer ceramic capacitor according to claim 1, wherein The amount of Mg included in the interface adjacent region is 0.8 atomic % to 4.2 atomic % based on the total amount of components of the interface adjacent region of the dielectric layer.
9. The multilayer ceramic capacitor according to claim 1, wherein: The interface adjacent region of the dielectric layer also includes Ba, Ti, Ni, Dy, Tb, Mn, V, Al, Si, Sn, O or a combination thereof.
10. The multilayer ceramic capacitor according to claim 9, wherein The interface adjacent region of the dielectric layer comprises Ti, and The amount of Mg included in the interface adjacent region of the dielectric layer is 5.0 parts by mole to 29.7 parts by mole based on 100 parts by mole of Ti in the interface adjacent region of the dielectric layer.
11. A method for manufacturing a multilayer ceramic capacitor, comprising: preparing a dielectric slurry by mixing a barium titanate-based main component powder and a secondary component powder including a Mg-containing compound; manufacturing a dielectric green sheet by using the dielectric slurry, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet laminate by laminating the dielectric green sheets on which the conductive paste layers are formed; manufacturing a capacitor body including a dielectric layer and an internal electrode layer by firing the dielectric green sheet laminate; and forming external electrodes on the capacitor body, wherein the capacitor body includes at least one missing portion, the missing portion being defined as a region where the continuity of the inner electrode layer is broken, and the missing portion includes a Mg concentrated region, the Mg concentrated region including Mg as a main element, The dielectric layer includes an interface adjacent region, the interface adjacent region being defined as a region from an interface between the dielectric layer and the inner electrode layer to a position in the dielectric layer at a depth of 80 nm to 100 nm, and the interface adjacent region includes Mg, and An atomic percentage content of Mg included in the interface adjacent region of the dielectric layer is lower than an atomic percentage content of Mg included in the Mg concentrated region of the missing portion.
12. The method according to claim 11, wherein: The Mg-containing compound is mixed in an amount of 0.01 parts by mol to 3 parts by mol based on 100 parts by mol of the barium titanate-based main component powder.
13. The method according to claim 11, wherein: The secondary component powder further includes a Dy-containing compound, a Tb-containing compound, a Mn-containing compound, a V-containing compound, an Al-containing compound, a Si-containing compound, a Sn-containing compound or a combination thereof.
14. The method according to claim 13, wherein: Based on 100 parts by mole of the barium titanate-based main component powder: The amount of the Dy-containing compound is 0.01 to 5 parts by mole, The amount of the Tb-containing compound is 0.01 to 5 parts by mole, The amount of the Mn-containing compound is 0.01 to 5 parts by mole, The amount of the V-containing compound is 0.01 to 5 parts by mole, The amount of the Al-containing compound is 0.01 to 5 parts by mole, The amount of the Si-containing compound is 0.01 to 5 parts by mole, and The amount of the Sn-containing compound is 0.01 parts by mole to 5 parts by mole.
15. The method according to claim 11, wherein: The conductive paste layer is made of a conductive paste including Ni.
16. A method of manufacturing a multilayer ceramic capacitor, comprising: preparing a dielectric slurry by mixing a barium titanate-based main component powder and a secondary component powder including a Mg-containing compound; manufacturing a dielectric green sheet by using the dielectric slurry, and forming a conductive paste layer on a surface of the dielectric green sheet; manufacturing a dielectric green sheet laminate by laminating the dielectric green sheets on which the conductive paste layers are formed; manufacturing a capacitor body including a dielectric layer and an internal electrode layer by firing the dielectric green sheet laminate; and forming external electrodes on the capacitor body, Here, the dielectric green sheet stack is fired at a firing temperature of 1150° C. to 1250° C. and a hydrogen concentration of 0.8% or less.
17. The method according to claim 16, wherein: The Mg-containing compound is mixed in an amount of 0.01 parts by mol to 3 parts by mol based on 100 parts by mol of the barium titanate-based main component powder.
18. The method according to claim 16, wherein: The secondary component powder further includes a Dy-containing compound, a Tb-containing compound, a Mn-containing compound, a V-containing compound, an Al-containing compound, a Si-containing compound, a Sn-containing compound or a combination thereof.
19. The method according to claim 18, wherein: Based on 100 parts by mole of the barium titanate-based main component powder: The amount of the Dy-containing compound is 0.01 to 5 parts by mole, The amount of the Tb-containing compound is 0.01 to 5 parts by mole, The amount of the Mn-containing compound is 0.01 to 5 parts by mole, The amount of the V-containing compound is 0.01 to 5 parts by mole, The amount of the Al-containing compound is 0.01 to 5 parts by mole, The amount of the Si-containing compound is 0.01 to 5 parts by mole, and The amount of the Sn-containing compound is 0.01 parts by mole to 5 parts by mole.